Issues of Implementation of Innovative Technologies in Science and Education - Umirova Dildora Shavkatovna (International Journal on Integrated Education, 2023)
This article describes about the importance of innovative educational technologies in advanced educational conditions. Information was also given on ways to make education more effective, and how to use modern technologies during the lesson.